Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

How would I find the limit for:

$$\lim_{n\to\infty}\left(\frac{n-1}{n}\right)^n$$

I know it approaches $\frac{1}{e}$, but I have no idea how it works. Plus, why does: $$\lim_{n\to\infty}\left(\frac{n-x}{n}\right)^n=\frac{1}{e^x}$$

share|improve this question
    
Have a look at this: math.stackexchange.com/questions/115863/… –  matt Mar 27 '12 at 9:35
    
How has $e$ been defined to you? –  Américo Tavares Mar 27 '12 at 9:57
    
e = $\lim_{n\to\infty}{(\frac{n+1}{n})^n}$ –  user27251 Mar 27 '12 at 10:00
    
Thanks for the information. And is $n$ an integer? I assume it is. Would you mind confirming? –  Américo Tavares Mar 27 '12 at 10:13
1  
@user27251 Hint: $\frac{n-1}n = \frac 1{\frac n{n-1}}$ –  martini Mar 27 '12 at 10:56

5 Answers 5

  1. (See martini's comment). For the first question write $\frac{n-1}{n}$ as $$\begin{equation*} \frac{n-1}{n}=\frac{1}{\frac{n}{n-1}}. \end{equation*}$$ Apply limits and use the definition of $\mathrm{e}$ you have been given $$\begin{equation*} \mathrm{e}=\lim_{n\rightarrow \infty }\left( \frac{n+1}{n}\right) ^{n}. \end{equation*}$$ We have $$\begin{eqnarray*} \lim_{n\rightarrow \infty }\left( \frac{n-1}{n}\right) ^{n} &=&\lim_{n\rightarrow \infty }\frac{1}{\left( \frac{n}{n-1}\right) ^{n}}= \frac{1}{\lim_{n\rightarrow \infty }\left( \frac{n}{n-1}\right) ^{n}} \\ &=&\frac{1}{\lim_{n\rightarrow \infty }\left( \frac{n+1}{n}\right) ^{n+1}}= \frac{1}{\lim_{n\rightarrow \infty }\left( \frac{n+1}{n}\right) ^{n}\cdot\lim_{n\rightarrow \infty }\frac{n+1}{n}} \\ &=&\frac{1}{\mathrm{e}\cdot 1}=\frac{1}{\mathrm{e}}. \end{eqnarray*}$$
  2. Hint for the second question: write $$\begin{equation*} \left( \frac{n-x}{n}\right) ^{n}=\left( \left( 1-\frac{1}{n/x}\right) ^{n/x}\right) ^{x}, \end{equation*}$$ use the substitution $m=n/x$ and apply limits.
share|improve this answer

One of the basic properties of $e$ is that $$ \lim_{ n \to \infty} \left(1+\frac{1}{n} \right)^n=e$$

You can use this here to find your answer.

share|improve this answer

For the first, take the reciprocal and substitute $n\mapsto n+1$ to get $$ \begin{align} \frac{1}{\lim\limits_{n\to\infty}\left(\frac{n-1}{n}\right)^n} &=\lim_{n\to\infty}\left(\frac{n}{n-1}\right)^n\\ &\stackrel{n\to n+1}{=}\lim_{n\to\infty}\left(\frac{n+1}{n}\right)^{n+1}\\ &=\lim_{n\to\infty}\left(1+\frac{1}{n}\right)^n\cdot\lim_{n\to\infty}\left(1+\frac{1}{n}\right)\\ &=e\cdot1 \end{align} $$ Therefore, $\lim\limits_{n\to\infty}\left(\frac{n-1}{n}\right)^n=\dfrac1e$.

For the second, take the reciprocal and substitute $n\mapsto nx+x$ to get $$ \begin{align} \frac{1}{\lim\limits_{n\to\infty}\left(\frac{n-x}{n}\right)^n} &=\lim_{n\to\infty}\left(\frac{n}{n-x}\right)^n\\ &\stackrel{n\to nx+x}{=}\lim_{n\to\infty}\left(\frac{nx+x}{nx}\right)^{nx+x}\\ &=\lim_{n\to\infty}\left(1+\frac{1}{n}\right)^{nx}\cdot\lim_{n\to\infty}\left(1+\frac{1}{n}\right)^x\\ &=e^x\cdot1 \end{align} $$ Therefore, $\lim\limits_{n\to\infty}\left(\frac{n-x}{n}\right)^n=\dfrac{1}{e^x}$.

We could have started from the second and set $x=1$ for the first.

share|improve this answer

I do the first part and the second part is done similarly.

Solution 1 We know that the derivative of $\ln x$ is $\frac{1}{x}$. Hence using first principle differentiation, we have: $$ \begin{align*} \frac{1}{x}&=\lim_{h\to0}\frac{\ln(x+h)-\ln x}{h}\\ &=\lim_{h\to0}\ln\left(1+\frac{h}{x}\right)^{\frac{1}{h}} \end{align*} $$ Let $n=\frac{1}{h}$ and $y=\frac{1}{x}$, so now $$ y=\lim_{n\to\infty}\ln\left(1+\frac{y}{n}\right)^n $$ Now let $y=-1$, then $$ \begin{align*} -1&=\lim_{n\to\infty}\ln\left(1-\frac{1}{n}\right)^n\\ \frac{1}{e}&=\lim_{n\to\infty}\left(1-\frac{1}{n}\right)^n \end{align*} $$

Solution 2 Use L'Hopital's rule: $$ \begin{align*} \lim_{n\to\infty}n\ln \left(1-\frac{1}{n}\right)&=-\lim_{n\to\infty}\frac{1}{1-\frac{1}{n}}\\ &=-1 \end{align*} $$ The rest is like solution 1.

share|improve this answer
    
ln is not additive. –  Bonanza Mar 27 '12 at 14:50
2  
What does that have to do with my solution? –  Vafa Khalighi Mar 27 '12 at 23:47

Here's a good strategy, first do the limit of the log of expression.

Let $y = \left(1 - \frac{x}{n} \right)^n$ (which is the same as your expression). Then, take the natural log of both sides to get $$\ln y = \ln \left[\left(1 - \frac{x}{n} \right)^n \right] = n \cdot \ln \left(1 - \frac{x}{n} \right) = \frac{\ln \left(1 - \frac{x}{n} \right)}{\frac{1}{n}}$$ Now, as $n \to \infty$, the final fraction goes to $\frac{0}{0}$, an indeterminate form. This suggests that we try l'Hopital's rule. That is

$$\begin{align*} \lim_{n \to \infty} \ln y &= \lim_{n \to \infty} \frac{\ln \left(1 - \frac{x}{n} \right)}{\frac{1}{n}} \\ &= \lim_{n \to \infty} \frac{\left(1 - \frac{x}{n}\right)^{-1} (x \cdot n^{-2})}{-n^{-2}} \\ &= \lim_{n \to \infty} -x\left(1 - \frac{x}{n} \right)^{-1} \\ &= -x \end{align*}$$

Therefore, since the exponential function $\exp(x) = e^x$ is continuous, we can move the limit in or outside of this function (by the definition of continuity) and thus find the limit of $y$ itself:

$$\lim_{n \to \infty} y = \lim_{n \to \infty} \exp(\ln y) = \exp \left( \lim_{n \to \infty} \ln y \right) = \exp (-x) = e^{-x}$$

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.